Synergistic Partnership Model to improve the Quality Management of Religiously Affiliated High Schools in Central Kalimantan, Indonesia - Fransiskus Janu Hamu; Sukestiyarno Sukestiyarno; Tri Joko Raharjo; Titi Prihatin (Research Horizon, 2021)
This study aims to describe the implementation of school partnerships, benefits, supporting factors, and inhibitors associated with the quality of Catholic High School education in Central Kalimantan Province. The study uses a qualitative approach and is conducted on a small scale. The sample consisted of 20 people, namely principals, teachers, parents, alumni desks, school committees, and the government. All information belongs to 5 Catholic Senior high schools in Central Kalimantan Province in Indonesia. All informants agreed to follow the study. Information collected from study participants used semi-structured interviews. The results showed that the synergistic partnership model has not been applied in the scope of Catholic Senior High School educational institutions in Central Kalimantan Province The participation of parents, communities, alumni ties, the government, and industry is very low due to limited access and lack of information about the existence of schools. Exclusive attitude and minder become a factor inhibiting the relationship of partnerships with stakeholders. The emergence of awareness on the part of the school of its limitations captures opportunities to build partnerships with stakeholders.